Measuring Quality Of Wireless LAN Using Quality Of Service (QoS) Approach - Aliy Hafiz (Saburai International Journal of Social Sciences and Development, 2021)
The internet has a very important role in education. Many activities are done through internet network. AMIK DCC Bandar Lampung is an educational institution that uses the internet as one of the supporting facilities and infrastructures to manage and organize the data and information used by the student to find references about the lecture. There are three buildings on the main campus building A building B and C buildings, where each building using wireless LAN to deploy internet access. There are some complaints submitted by students related wireless network encourage researchers to study the quality of service wireless LAN. Thus the researchers wanted to analyze the Quality of Service wireless LAN networks in building A, building B, and C, in each floor. The method used in this research is Quality of Services (QOS). Where an analysis wireless network by four parameters. There are namely delay, packet loss, bandwidth, and throughput. The results of the measurement and monitoring of Quality of Service wireless LAN at AMIK DCC Bandar Lampung in building A, building B, C on each floor of the building can be classified in the category of poor, and the factors that occurred in the signal range cannot cover every room in every building and have not bandwidth management.